GREENING THE CURRICULUM FOR DEVELOPING SUSTAINABLE DISASTER MANAGEMENT COMPETENCIES AMONG STUDENTS THROUGHNURTURING GREEN CULTURE BEHAVIOUR - Alias Musthafa., M N Mohamedunni; Stephen, Rini E (International Journal of Psychosocial Rehabilitation, 2020)
The prime objective of curriculum is to enable the future citizens of the society the smooth adjustment with the changing socio-cultural demands. As the existence of human kinds itself is under threat the students have to be trained in dealing with the emergency situations at day to day life. Indiscriminate interference of man with nature has proved its consequenceswhich adversely affect even the existence of man. Various kinds of disasters threaten the existence of mankind on earth. Many of these disasters are the consequence of reckless activities and uncontrolled interventions of human on nature. The possible solution for this is greening the curriculum. Curriculum must nurture green culture behaviour among the students that enable students using nature as a learning tool to focus on real-world problems. Developing green curricular activities is a promising approach to make the young generation with proper environmental awareness and enhance nature friendly behaviour among them. This paper stresses the significance of green curricular approaches for disaster management education. Rather than just converting the institutions as shelter places for the refugees or victims of disasters, the school should be metamorphosed to nodal centres of disaster management both in principle and practices.